Rhapsodie et métamorphoses de la voix dans The War Plays d’Edward Bond - Eléonore Obis (Sillages Critiques)
The War Plays are a trilogy written by Edward Bond and completed in 1985. These plays represent a major aesthetic turning point in his work. They are structured and written with what the French critic Jean-Pierre Sarrazac calls a “rhapsodic” dynamic: questioning all the main elements that make a play, the trilogy calls theatre into question. Bond’s strategy is, among others, to try to redefine the concept of character, and hence question the origin and authority of the voice. The changing voices of The War Plays are a sign of the major metamorphoses Bond’s theatre underwent at the end of the 80s.